PENGARUH PENAMBAHAN WORTEL DAN RUMPUT LAUT TERHADAP KUALITAS NUGGET TEMPE - FIRDAUS, FIRDAUS; Faridah, Anni; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2014)
The purpose of the study is to analyze the effect of the addition of carrot and seaweed as much as 25%, 50%, 75% and 100% of the amount of material used to quality tempe nuggets (shape, color, aroma, texture, and flavor). Type of research is true experimental with completely randomized design method. The object of research is tempe nuggets with the addition of carrots and seaweed were: 0%, 25%, 50%, 75% and 100%. The data used are primary data obtained directly from the 30 panelists who gave the answer of organoleptic test format. The data has been obtained and tabulated in tables and performed Variant Analysis (ANAVA), if different followed by Duncan test. The results showed significant effect on the quality of the same form, star shape, the color of the inside, the texture elasticity, hardness and hedonic texture, aroma tempeh, carrots and hedonic aroma, not unpleasant taste and savory flavor. Statistical test results showed a sub indicator of skin color, hedonic color, fragrant aroma and hedonic taste fried tempe nuggets Ha rejected stating there was no significant effect of the addition of carrots and seaweed on the quality of tempe nuggets.Keywords: Tempe Nugget, Carrot, Seaweed